Calcareous foraminifera from tropical north Queensland, Australia: their usefulness as proxy sea-level indicators in the absence of fossil agglutinated foraminifera - Woodroffe, Sarah; Horton, Ben (Anuário do Instituto de Geociências, 2006)
Abstract